PERAN KEPALA DESA DALAM MENINGKATKAN KINERJA APARAT DESA MOPUYA KECAMATAN BULAWA KABUPATEN BONE BOLANGO - Muh Firyal Akbar (Publik : (Jurnal Ilmu Administrasi), 2015)
This research aimed to know the role of the head of village in improving the performance of officials Mopuya village in sub district of Bulawa, Bone Bolango regency, to know the factors that impede improvement performance of officials Mopuya village in sub district of Bulawa, Bone Bolango regency. While the benefits of research for academics, are expected to be the brainstorming of knowledge and information that can be used as a reference or grounding in any steps strategy of head village, the practical benefit, that is to increase the knowledge and training to think systematically and bringing insight into the role of head of village in improving the performance of officials village. The research approach used in this research is the phenomenological approach implies that an approach where the researchers trying to understand the meaning of the events of research and its relation to officers who investigated the ordinary people in a particular situation, or the type of research is used descriptive qualitative research.The result of research showed that is the role of the head of village in improving the performance of officials Mopuya village than do the good role with through 4 roles that already been implemented by the head of village. While the factors that impede improvement performance of officials Mopuya village that is the terms of attendance is not on time, lack of knowledge about computers, lack of communication and lack of self-awareness of the officials that not active.